2019
DOI: 10.3390/su11236534
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Eco-Labeled Food in Forests: Integrated View from South Korea

Abstract: Due to global interest in the improvement of national income and quality of life, eco-labeled food (ELF) for sustainable consumption and personal healthcare has been increasing. This study aims to contribute to two research streams by examining the quality of ELF in forests (ELFF). First, this study intends to estimate the willingness to pay (WTP) of ELFF producers for the certification verified by the government-supported institution and investigate the difference in certification costs between the actual cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Accordingly, focusing on a single specific service [7] or bundles of multiple services [24] are both appropriate. Many previous studies have focused on one specific ES, such as the following: provisioning clean non-timber forest products [25], the conservation of biodiversity [26], carbon absorption [27], regulating local climates [28], and fostering water resources [29]. Investigating the effect of one specific ES on human life is essential for understanding the relationship between the resource and its use from a human's perspective.…”
Section: Payment For Es Of Local Forestmentioning
confidence: 99%
“…Accordingly, focusing on a single specific service [7] or bundles of multiple services [24] are both appropriate. Many previous studies have focused on one specific ES, such as the following: provisioning clean non-timber forest products [25], the conservation of biodiversity [26], carbon absorption [27], regulating local climates [28], and fostering water resources [29]. Investigating the effect of one specific ES on human life is essential for understanding the relationship between the resource and its use from a human's perspective.…”
Section: Payment For Es Of Local Forestmentioning
confidence: 99%
“…Restrictions imposed for conservation may affect farming practices. However, with the provision of production and marketing history and the introduction of green labeling, ecological labeling, conservation labeling, friendly labeling, and organic labeling, consumers' WTP can usually be increased, and product awareness could also be raised [17,33,34]. A study on French consumers' WTP for apples with different labels showed that labeled apples increased different consumer groups' WTP [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Under the probit model: (4) the annual WTP per capita for cooperation with farmers for pangolin conservation programs is NTD 1729.00−1698.97 (about 61.70 USD); and (5) the annual WTP per capita for continuous pangolin studies is NTD 1479.09−1439.37 (about 52.49 USD). More and more studies have found a positive WTP for labelled food products [14,33,34]. Therefore, eco-labelling might play a role in gaining added value for food items and influencing the relative importance of their price.…”
mentioning
confidence: 99%